How do you simplify #(6x^2)^4#?

1 Answer
May 22, 2018

Answer:

See a solution process below:

Explanation:

First, use this rule of exponents to rewrite the term within the parenthesis:

#a = a^color(red)(1)#

#(6x^2)^4 => (6^color(red)(1)x^2)^4#

Now, use this rule of exponents to simplify the expression:

#(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#

#(6^color(red)(1)x^color(red)(2))^color(blue)(4) =>#

#6^(color(red)(1) xx color(blue)(4))x^(color(red)(2) xx color(blue)(4)) =>#

#6^4x^8 =>#

#1296x^8#